Desenvolvimento de formulações para potencializar a ação de metabólitos de Phoma dimorpha no controle biológico de plantas daninhas - Chaves Neto, José Roberto (2019)
In the last decades, the agricultural sector has faced many difficulties due to damage caused by the presence of weeds in several crops, causing significant losses in food production. Among the alternatives for reducing losses, stands out the biological control based on the use of biosynthesized secondary metabolites by microorganisms, being the group of endophyte fungi the most used. In addition to concentration of these metabolites, it is necessary to determine the formulation processes that provide the final product with stability, wettability, spreadability and plant penetration. Thus, the general objective of this work was to develop formulations to enhance the action of fermented broth from Phoma dimorpha concentrate concentrated by membrane separation processes in biological weed control. Evaluating the efficacy and viability of three methods of preserving isolates of this fungus (periodic subcultures, Castellani and filter paper fragments), in two evaluation periods; to evaluate the efficiency of the use of different methods for overcoming seed dormancy of rice grass (Echinochloa spp.), purple amaranth (Amaranthus cruentus), black-jack (Bidens pilosa) and sicklepod (Senna obtusifolia) weeds, produce bioactive compounds from submerged fermentation of P. dimorpha; concentrate the bioactive compounds present in the crude fermentation broth of P. dimopha by ultrafiltration (UP010), microfiltration (MP005) and nanofiltration (NP010) membranes and investigate the effectiveness of the crude fermentation broth of P. dimorpha fungus from permeate and retentate fraction and formulations in the biological control of different plant species: cucumber (Cucumis sativus), rice grass (Echinochloa spp.), purple amaranth (Amaranthus cruentus), black-jack (Bidens pilosa) and sicklepod (Senna obtusifolia). Based on the results it was observed that the filter paper fragment was the most effective method for preserving P. dimorpha isolates. To overcome weed seed dormancy, it was found that the mechanical scarification method with sandpaper was the most efficient for Senna obtusifolia; for Bidens pilosa, Echinochloa sp. and Amaranthus cruentus the most efficient method was soaking in water for 48 hours. Regardless of membrane used in fermentation broth concentration process, the surface tension of retentate fraction was reduced to below the broth values. It was also found that the concentration intensified the phytotoxic effect of concentrated broth (retentate fraction) on detached leaves of C. sativus independent of membrane used. The concentrated broth (retentate fraction) formulations from each membrane, regardless of vegetable oil and target weed species, caused injuries, from small spots, yellowing and leaf necrosis, to damage to apical bud, growth paralysis and by end plant death.